Fenología de cinco especies coexistentes de Cedrela (Meliaceae) en el valle de Chanchamayo, Junín - Perú - Terreros-Camac, Sara (2025)
The genus Cedrela contains timber species of great economic value that are ecologically and so- cially important in neotropical ecosystems. Phenological studies of Cedrela species have not been reported in the central Peruvian rainforest. The objective of this research was to preliminarily re- cord the phenological behavior of five sympatric species of the genus Cedrela in the Chanchamayo Valley (Junín), central Peru. The species evaluated were Cedrela angustifolia Moc. & Sessé ex DC., domatifolia W.Palacios, C. fissilis Vell., C. montana Turcz. and C. odorata L. Three phenophases were documented monthly: tender structures (budding), maturity and overmaturity (senescence) throughout one year (2021-2022) relating them to the dry and rainy seasons, and herbarium spe- cimens. Senescence and leaf fall occurred in the rainy (October to April) and dry (May to Septem- ber) seasons, flowering at the beginning of the rainy season and fruiting in the rainiest months, except for C. odorata and C. fissilis which flowered and fructified throughout the year. Two types of phenological behavior were observed: non-seasonal for C. odorata and C. fissilis; and seasonal for C. domatifolia, C. angustifolia and C. montana. These behaviors could represent a reproductive isolation strategy that requires further study.